Sistem Pemantauan dan Pengendalian Kinerja Beban Listrik Melalui Telegram - Ruman, Oktavianus; Setiawan , Aries Boedi; Sari , Resi Dwi Jayanti Kartika Sari (Politeknik Negeri Malang, 2025)
The advancement of Internet of Things (IoT) technology has enabled the development of smarter and more efficient electrical systems. In this research, a smart meter system was designed and built using the ESP8266 microcontroller, PZEM-004T sensor, and relay module, integrated with the Telegram application. The system can monitor electrical parameters such as current, voltage, power, and energy consumption (kWh) in real-time, as well as providing remote load control features. The PZEM-004T sensor is used to accurately measure electrical parameters, while the relay functions as an additional protection mechanism against overcurrent conditions, with a current threshold of 2 Amperes. The system is also designed to automatically send daily energy consumption reports and cost estimates via Telegram. Test results show that the system can read data with high accuracy (relative error < 5%) and can automatically or manually control the power load via Telegram. Real-time notifications, energy reporting, and cost estimation features make this system effective for practical and economical electricity monitoring and control.